A meta-analysis of the impact of rail stations on property values: Applying a transit planning lens. (September 2022) - Rennert, Lindiwe
Highlights: Introduction of 10 new variables to the rail access uplift meta-analysis literature. Transit expenditure share and network expanse positively impact rail access premiums. Rent control policies and ethno-racial dynamics affect rail access premiums. Tests effects of Global Financial Crisis (2007–2009) on rail access premiums. Expansion of geo-scope of rail access premium comparisons; includes Global South. Abstract: Access to transit infrastructure is valuable. In areas surrounding rail stations, some of that value gets absorbed by property markets. Since 1970, over 200 case studies worldwide have explored the extent to which transit access impacts property value uplift. However, findings from this body of research vary widely. In an attempt to explain this variation, previous meta-analytic studies have focused on testing the roles that built environment elements, temporal factors, and modelling techniques play in shaping the observed relationship between proximate positioning from rail stations and property pricing. This study expands on these meta-analyses by introducing the first examination of how transit service elements – e.g. frequency, fare, reliability – impact rail-induced residential property value uplift. It further contributes to the literature by expanding the range of geo-comparability of uplift findings across four continents, examining the potential effects of the Global Financial Crisis of the late 2000s, and adding 10 new variables of potential influence not only under the banner of 'transit service', but pertaining to neighborhood socio-demographics and housing policy as well. Findings reveal that factors of geography, housing data type, race and ethnicity, rent control policies, rail type, transit cost, and transit network expanse all significantly affect rail access uplift magnitude ranging from depreciating effects of 7.4 percentage points to appreciating effects of 9.6 percentage points. Beyond helping to explain variation across the literature, these findings can be a useful tool for policymakers combatting trends of increasing market-driven displacement from transit-rich areas, those pursuing financing mechanisms for transit infrastructure, and to transit planners concerned with how their decisions may affect matters of housing equity for the communities they serve.